THE CONTRIBUTION OF BOARDING SCHOOLS IN ECONOMIC EMPOWERMENT LOCAL COMMUNITIES - Ahmad Munib Syafa’at; Nur Mu’alina; Nur Anim Jauhariyah (FORPIM PTKIS ZONA TAPAL KUDA, 2023)
The role of Islamic boarding schools in the form of community empowerment in substance leads to a means of establishing communication between Islamic boarding schools and the surrounding community. The purpose of this study is to describe the contribution of Islamic boarding schools which are one of the indicators of community empowerment at the Darussalam Blokagung Islamic Boarding School in Banyuwangi Regency. This study uses a descriptive qualitative approach with in-depth interviews with caregiver informants and the surrounding community using SWOT analysis. The results of the research show that the development of economic empowerment products for students and the community through UMKM by utilizing natural resources around the pesantren is a step in preserving local products so that the surrounding community who are involved in the agricultural, fishery and other sectors will be able to distribute their crops to the pesantren so that the food needs of students can be met by the surrounding community.